Perbandingan Sistem Ketatanegaraan Denmark dan Swedia: Kajian atas Monarki Konstitusional di Era Modern - Kallyca Puspa Ayu; Nazifa Ailuf Efendi; Rifai, Rifai; Zaky Walad (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This study examines the constitutional systems of Denmark and Sweden as two of the most stable and advanced models of modern constitutional monarchy in the world. While maintaining the institution of monarchy, both countries have successfully integrated the principles of parliamentary democracy, parliamentary supremacy, and strict limitations on executive power, so that the monarch plays a purely symbolic role in the state. Using a normative-comparative legal research method that focuses on the 1953 Danish Constitution and the 1974 Swedish Instrument of Government, this study traces the historical evolution, constitutional structure, mechanisms of government formation, legislative oversight, and the role of the judiciary in both countries. The results of the study show that Denmark has retained a number of historical formulations regarding the power of the king in the text of the constitution, but all of these powers are symbolic in nature because they are controlled by parliamentary convention. Sweden, through its 1974 reforms, opted for a more decisive model by explicitly removing all political roles of the monarchy. Despite differences in constitutional design, both countries share fundamental similarities in their egalitarian political culture, bureaucratic professionalism, political consensus, and parliamentary rule mechanisms that create governmental stability.Further analysis shows that the continuity of the monarchy in both countries is inseparable from peaceful historical transformation, the monarchy's ability to adapt to democratization, and its role as